Association of primary dysmenorrhea with socio-economic status and education level in patients attending gynaecology OPD in a tertiary care centre: a questionnaire-based study - Sethi, Nimrata; Puri, Sapna; Jamwal, Narita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Dysmenorrhea is defined as painful menstrual cramps of uterine origin which is often accompanied by low backache, nausea and vomiting, headache, or diarrhoea. Primary dysmenorrhea defines cyclic menstrual pain without an identifiable associated pathology. Methods: This cross-sectional study was conducted among patients attending gynaecology OPD of ASCOMS and Hospital. Data was collected using a pretested structured self-administered questionnaire. Aim was to study the association of primary dysmenorrhea with socio-economic status and educational status in patients attending gynaecology OPD in ASCOMS and hospital. Results: A total of 584 patients participated in the study with age between 20-40 years. 409 (70%) of the patents suffered from primary dysmenorrhea. Patients who belonged to upper socioeconomic status were 2.71 times more likely to experience primary dysmenorrhea as compared to those who belonged to lower socioeconomic class (AOR 2.71, 95% CI (1.41, 5.16)) and the result was found to be statistically significant. However, the educational status of the patient was not significantly associated with the prevalence of dysmenorrhea. Conclusions: Participants belonging to the upper socioeconomic status were found to be more severly affected with primary dysmenorrhea than those who belonged to the lower socioeconomic status. Thus, we conclude that primary dysmenorrhea can be considered as a psychosomatic disorder. It needs counselling and stress management education as a first line management rather than any pharmacological treatment.